A Review of Mixed Matrix Membranes in Gas Separation - M. A., Faiz; Iqbal, Ahmed; Zulkafli, Hassan (2009)
The aim of this research is for the separation of oxygen from sulfur dioxide (SO2) and carbon dioxide (CO2) is preparing a novel mix matrix membrane (MMC) using novel microwave technique. Mix membrane polymer can develop, by using PVDF (Polyvinylidene Fluoride) and Polycarbonate (PC). The performance of the mix membrane polymer will evaluated in terms of the separation rate of oxygen. In order to investigate the influence of microwave technique on the mechanism of mix membrane polymer; FTIR, NMR will performed. In addition the membrane morphology and structure will examined using SEM, FTIR and NMR. The gas separation properties will be measure using lab scale test rig.